Evaluation of Reliability of Ultrasonographic Parameters in Differentiating Benign and Metastatic Cervical Group of Lymph Nodes - Raja Lakshmi, Chintamaneni (Hindawi Publishing Corporation, 2014)
The aim of the current study is to determine the efficacy of ultrasound in differentiating between benign and metastatic group of cervical lymph nodes. The study included forty-five subjects who were divided into three groups with 15 in each, by stratified random sampling method. Group 1 comprised fifteen patients without signs and symptoms of any infection and neoplasms in head and neck region (control group). Group 2 included fifteen patients with signs and symptoms of malignancy in head and neck region. Group 3 consisted of fifteen patients with signs and symptoms of odontogenic infections. “MY LAB-40” ultrasound machine with linear array transducer of 7.5 MHZ frequency was used for detecting cervical lymph nodes following Hajek's classification. The patients further underwent ultrasound guided FNAC under standard aseptic protocol and samples were subjected to cytopathological evaluation. Chi square analysis and one way ANOVA test were applied to obtain the results. We concluded that ultrasound and USG FNAC can be used accurately to assess the status of lymph nodes. The ultrasonographic features of lymph nodes with round shape, absence of hilar echo, sharp nodal borders, hyperechoic internal echogenicity, and presence of intranodal necrosis were highly suggestive of metastatic cervical lymph nodes.